Edukasi Manfaat Bit-Lemon dan Sereh-Lemon Dalam Mengatasi Anemia Pada Ibu Hamil dan Pemulihan Ibu Masa Nifas - Gustina, Irwanti; Rahma Anandita, Mella Yuria; Djami, Moudy Emma Unaria (Yayasan Sagita Akademia Maju, 2025)
Currently, herbal medicine is an alternative choice that is of interest to people in various parts of the world. Especially Indonesia, as one of the countries rich in crops, Indonesia began to utilize herbal plants to be managed as an alternative in the treatment of various disease complaints. There are several herbs and spices used in Indonesia, including beetroot, lemon and lemongrass, which have been proven to be used in overcoming anemia in pregnant women and can help the postpartum recovery process and prevent postpartum bleeding. The purpose of this activity is to provide education to the community about the benefits of herbal plants for the treatment of anemic pregnant women and postpartum recovery. The activity was carried out at Posyandu Bugenville in dukuh village. The results of the activity obtained increased community knowledge about the benefits of herbal plants beet-lemon and sere-lemon for improving community health.